PENINGKATAN KEMAMPUAN MENGIDENTIFIKASI UNSUR-UNSUR INTRINSIK CERITA PENDEK MELALUI MODEL RESPONS ANALISIS SISWA KELAS XI IPA2 SMA NEGERI 1 CENDANA KABUPATEN ENREKANG [Increasing Ability to Identify Intrinsic Elements of Short Stories Through the "Response Analysis "Model of Class XI Students 2 of Cendana 1 Public High School in Enrekang Regency] - Syaidah Baharuddin (TOTOBUANG, 2018)
This study aims to describe the improvement of the learning process and learning outcomes identify the intrinsic elements of short stories through the "response analysis" model of class XI IPA 2 Cendana 1 Public High School, Enrekang Regency. This research was conducted in two cycles, each cycle took place 2 meetings and each cycle consisted of 4 stages, namely: planning, action, observation, and reflection. This research is a classroom action research with exposure to qualitative descriptive data and quantitative data. Qualitative data is obtained from the observation sheet of each implementation of the action (learning process), and quantitative data is obtained from the final test of each cycle. The subjects in this study were students of class XI IPA 2, amounting to 20 people. The action given is intended to find out in the form of improving the learning process and learning outcomes in the first cycle. The second cycle is in the form of corrective actions towards deficiencies experienced in the first cycle. The results of data analysis conducted on the results of the research in the first cycle and the second cycle concluded that, learning identifies intrinsic elements in students of class XI IPA 2 Cendana State High School 1 Enrekang District through the "response analysis" model can improve the learning process and learning outcomes identifying intrinsic elements of short stories.Penelitian ini bertujuan untuk mendeskripsikan peningkatan proses pembelajaran dan hasil pembelajaran mengidentifikasi unsur-unsur intrinsik cerita pendek melalui model respons analisis siswa kelas XI IPA 2 SMA Negeri 1 Cendana Kabupaten Enrekang. Penelitian ini dilaksanakan dalam dua siklus, setiap siklus berlangsung dua kali pertemuan dan setiap siklus terdiri atas empat tahap yaitu: tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Penelitian ini merupakan penelitian tindakan kelas dengan pemaparan data deskriptif kualitatif dan data kuantitatif. Data kualitatif diperoleh dari lembar observasi dari setiap pelaksanaan tindakan (proses pembelajaran), dan data kuantitatif diperoleh dari tes akhir setiap siklus. Subjek dalam penelitian ini adalah siswa kelas XI IPA 2 yang berjumlah dua puluh orang. Tindakan yang diberikan dimaksudkan untuk mengetahui berupa peningkatan proses pembelajaran dan hasil pembelajaran pada siklus pertama. Adapun siklus kedua berupa tindakan perbaikan terhadap kekurangan-kekurangan yang dialami pada siklus pertama. Hasil analisis data yang dilakukan terhadap hasil penelitian pada siklus pertama dan siklus kedua disimpulkan bahwa, pembelajaran mengidentifikasi unsur-unsur intrinsik pada siswa kelas XI IPA 2 SMA Negeri 1 Cendana Kabupaten Enrekang melalui model respons analisis dapat meningkatkan kemampuan pada proses pembelajaran dan hasil pembelajaran mengidentifikasi unsur-unsur intrinsik cerita pendek.